(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2010)
Tuberculosis (TB) is a leading public health problem worldwide particularly in the developing countries. The HIV epidemic has increased the global tuberculosis burden. Estimating the proportion of HIV infection among TB cases can act as early warning system for the spread of TB due to HIV in the country. The objective of the study was to know status of TB/HIV co-infection cases among the TB patients at DOTS clinic in BPKIHS, Dharan, Nepal. Three Hundred newly diagnosed TB cases attended to BPKIHS DOTS clinic were tested for HIV. Among 300 newly TB patients, 14 (4.7%) patients were HIV positive. All were males. The study has shown very high (4.7%) TB/HIV co-infection. This is an alarming situation. Similar operational research can be conducted in different parts of Nepal to know the exact scenario of TB/HIV co-infection, which is necessary for formulating national policy & guidelines for TB/HIV control in the country. Keywords: TB & HIV Co-infection; TB; HIV; Nepal DOI: 10.3126/saarctb.v5i2.3072 SAARC J. Tuber. Lung Dis. HIV/AIDS 2008 Vol.5(2) 22-25